2017
DOI: 10.18332/tpc/74709
|View full text |Cite
|
Sign up to set email alerts
|

A picture is worth a thousand words: Electronic cigarette content on Instagram and Pinterest

Abstract: INTRODUCTION This study examined electronic cigarette (e-cig) content in visual materials posted on the social-media platforms Instagram and Pinterest. Both platforms allow users to upload pictures to the internet and share them globally. Users can search for pictures tagged with specific keywords and phrases. METHODS Using content analysis, this study identified themes in image postings of e-cigs on social media. During five weeks of data collection, keywords were used to identify pictures related to e-cigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 16 publications
(12 reference statements)
0
46
0
4
Order By: Relevance
“…Advertisements involving older individuals may have had a weaker effect; however, many ecigarette advertisements on social media are youth-friendly. 33 In summary, adolescents who reported using social media intensely in their daily lives and those who were randomized to view Instagram advertisements or posts with more e-cigarette content reported more positive attitudes toward e-cigarettes and had a greater likelihood of future use. Given that the vast majority of young people use social media regularly 7 and many are exposed to e-cigarette content on social media, 26,41 findings suggest a need to enforce and expand regulation of e-cigarette content.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 2 more Smart Citations
“…Advertisements involving older individuals may have had a weaker effect; however, many ecigarette advertisements on social media are youth-friendly. 33 In summary, adolescents who reported using social media intensely in their daily lives and those who were randomized to view Instagram advertisements or posts with more e-cigarette content reported more positive attitudes toward e-cigarettes and had a greater likelihood of future use. Given that the vast majority of young people use social media regularly 7 and many are exposed to e-cigarette content on social media, 26,41 findings suggest a need to enforce and expand regulation of e-cigarette content.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Instagram-type posts were developed based on content analyses of e-cigarette-related and general Instagram content. [30][31][32][33][34] E-cigarette posts depicted e-liquids, devices, and young e-cigarette users. [31][32][33][34] Unrelated posts reflected popular photo categories on Instagram: selfies, friends, travel, sports, food, fashion, or gadgets.…”
Section: Social Media Postsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instagram provides a platform for individuals to upload pictures and videos using hashtags as keywords. Keyword searches allow people to explore the images linked to the hashtags, and therefore, interact with the user-generated content [ 16 ]. E-cigarette content is popular on Instagram, and advertising companies characterize e-cigarettes as novel devices [ 16 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al [ 20 ] categorized Instagram photos about the electronic cigarette and found that advertisement was the most common type of content, followed by product and activity. The results of Lee et al [ 21 ] also revealed that the most popular category of Instagram posts of electronic cigarettes was marketing. Laestadius et al [ 22 ] examined what kind of user mainly posted about electronic cigarettes on Instagram; it was found that over half of the posts were uploaded by corporate users.…”
Section: Related Workmentioning
confidence: 99%